Occurrence of Proteinuria and its Predisposing Factors among Pregnant Women Attending Antenatal Care Clinic at St. Francis Hospital Nsambya. - John Edward Munyaga; David Serunjogi (Student's Journal of Health Research, 2020)
Background: Proteinuria refers to a condition where more than trace amounts of proteins are found in normal urine. Proteinuria is a defining dysfunction of pre-eclampsia Proteinuria is one of the cardinal indications of pre-eclampsia, a common and severe complication in pregnancy. Also, there are several factors responsible for its occurrence among pregnant women. The study aimed to establish the occurrence of proteinuria among pregnant women and to establish the predisposing factors of proteinuria among pregnant women attending antenatal care services in St. Francis Hospital Nsambya. Methodology:  This was a cross-sectional study where qualitative and quantitative data was collected. Participants' urine samples were taken off and analysed macroscopically, protein detection using uristics, and 25% SSA and then microscopic examination done once they had consented. Results:  Out of 96 participants, the occurrence of proteinuria was 9.4% (p = 0.094) and it was increasing with the increase in the age of the pregnant women. The predisposing factors to proteinuria in pregnancy were urinary tract infections (88.9%) (p = 0.889), hypertension (11.1%) (p = 0.111) and gestation age.  Conclusion and recommendation:  Clients who receive antenatal care services in St. Francis Hospital Nsambya antenatal clinic should routinely be screened for proteinuria. Wider research about proteinuria among pregnant women should be done to establish a more nationalistic occurrence. Health education should emphasize the importance of pregnant women reporting urinary tract infections after being empowered with its signs and symptoms even without pain. This is because urinary tract infections can lead to complications in pregnancy and could become fatal.